2015
DOI: 10.1002/2015ja021023
|View full text |Cite
|
Sign up to set email alerts
|

Azimuthal flow bursts in the inner plasma sheet and possible connection with SAPS and plasma sheet earthward flow bursts

Abstract: We have combined radar observations and auroral images obtained during the Poker Flat Incoherent Scatter Radar Ion Neutral Observations in the Thermosphere campaign to show the common occurrence of westward moving, localized auroral brightenings near the auroral equatorward boundary and to show their association with azimuthally moving flow bursts near or within the subauroral polarization stream (SAPS) region. These results indicate that the SAPS region, rather than consisting of relatively stable proton prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
31
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 45 publications
6
31
1
Order By: Relevance
“…Makarevich et al () used IMAGE FUV and radar data to present a case study in which they suggested that a strong enhancement of SAPS flows occurred in association with an auroral streamer. Similar results were found by Lyons et al (). If auroral streamers are commonly associated with SAPS intensification, it would imply that transient fast earthward plasma sheet flows are associated with westward SAPS flow enhancements.…”
Section: Introductionsupporting
confidence: 92%
“…Makarevich et al () used IMAGE FUV and radar data to present a case study in which they suggested that a strong enhancement of SAPS flows occurred in association with an auroral streamer. Similar results were found by Lyons et al (). If auroral streamers are commonly associated with SAPS intensification, it would imply that transient fast earthward plasma sheet flows are associated with westward SAPS flow enhancements.…”
Section: Introductionsupporting
confidence: 92%
“…Narrow channels of enhanced westward ion velocity (shown in green) were also observed roughly colocated with the minimum n e for all cases in which the Swarm EFI was operating. We also note that while SAID are reported between 16 and 2 hr MLT with the highest occurrence probability density around 22 MLT (He et al, 2014;Spiro et al, 1979), all Steve events presented so far have been between 22 and 2 MLT. It should be noted that because there are no v i measurements available for four of the events in Figure 1, they do not meet the criteria used in this study to identify SAID.…”
Section: Steve Measurements With Swarmmentioning
confidence: 53%
“…Here we applied a single-layer model with a fixed altitude of the layer at 350 km to all geographical latitudes, but we can also mention several other approaches which can be applied to retrieve vertical TEC at equatorial latitudes, particularly, using the higher-elevation cutoff mask [e.g., Paul et al, 2011;Sur et al, 2015] or using the modified dip latitude [e.g., Azpilicueta et al, 2006;Brunini and Azpilicueta, 2010]. As a result for each station we obtain TEC values along all visible (GPS or GLONASS) satellites with 30 s sampling period.…”
Section: Data and Methods Usedmentioning
confidence: 99%